THE DEVELOPMENT OF SOLAR ENERGY AND ITS EFFECTS ON REDUCING IMPORT DEPENDENCY IN THE REPUBLIC OF MOLDOVA - Vitalie TOMA; Boris COREȚCHI (Eastern European Journal of Regional Studies)
The purpose of this study is to analyze the evolution and current state of solar energy development in the Republic of Moldova, with a particular focus on its role in reducing dependence on imported energy resources. The study identifies two key findings: (1) the implementation of 434 MW of solar capacity could reduce electricity imports by approximately 16.5%, and (2) domestic production could increase from 27% to 39% of national consumption, strengthening energy security. A review of recent literature highlights that while Moldova has made progress in developing solar energy capacities, practical applications of decentralized and hybrid systems remain limited, with significant potential for expansion. The actual level of research and achievements in the field shows that Moldova is at an early-to-intermediate stage, with ongoing pilot projects, emerging regulatory frameworks, and increasing public and private investments. This research evaluates Moldova’s solar energy potential based on climatic and geographic data, examines existing policies and regulatory frameworks, and analyzes current investments and projects in the photovoltaic sector. The paper proposes concrete measures to stimulate the expansion of solar infrastructure, including financial incentives, public-private partnerships, and technological innovation. Ultimately, this study contributes to the development of a more sustainable, resilient, and energy-independent future for the Republic of Moldova